Vocational expectations and aspirations in Mexican-American school children - Brickman, Idel R. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study is concerned with vocational expectations and aspirations in Mexican-American eighth-grade children. The data were Ss’ responses to questionnaire items about their own expected and wished- for vocations and about their fathers’ vocations. The results, based on chi- square analyses, support hypotheses that expectations and aspirations are not equivalent (p<.001), that Mexican-American Ss express significantly (PC.001) lower levels of vocational expectations and aspirations when compared with those previously noted in other ethnic groups (Stephenson, 1957), and that the observed ethnic differences persist (p<.001) when the data are analyzed within socioeconomic lines (father’s occupational status). Implications for educational and vocational achievement are noted.